2015
DOI: 10.11604/pamj.2015.20.389.6202
|View full text |Cite
|
Sign up to set email alerts
|

Les tumeurs annexielles cutanées: étude anatomopathologique à propos de 96 cas

Abstract: Les tumeurs annexielles cutanées sont des tumeurs primitives cutanées à la fois rares et hétérogènes. Elles sont le plus souvent bénignes et rarement malignes. Elles sont dominées du point de vu morphologique par leur polymorphisme lésionnel. Le but de cette étude est de relever le profil épidémiologique et les différents aspects anatomopathologiques de ce groupe de tumeurs dans une cohorte de population marocaine et de les comparer avec les données de la littérature. Il s'agit d'une étude rétrospective de 96 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
(25 reference statements)
3
7
0
Order By: Relevance
“…The average age of our patients was 34 years old; this result is comparable to that reported by Gayathri et al that show the average age was 35.2% and Samaila et al with an average age with 33 years old. [9,10], considering the sex factor there was a slight male predominance (sex ratio of 1.15), which is consistent with the literature [1,5,8].…”
Section: Results:-supporting
confidence: 92%
See 2 more Smart Citations
“…The average age of our patients was 34 years old; this result is comparable to that reported by Gayathri et al that show the average age was 35.2% and Samaila et al with an average age with 33 years old. [9,10], considering the sex factor there was a slight male predominance (sex ratio of 1.15), which is consistent with the literature [1,5,8].…”
Section: Results:-supporting
confidence: 92%
“…The Adnexal skin tumors are abnormal and consist of many types. The world health organization divided these types of tumors to 21 subtypes benign and 15 subtypes malignant tumors [1,2]. They can be presented in different varieties such as follicular, eccrine, apocrine, sebaceous and sometimes mixed differentiation, making the diagnostic difficult [1,5].…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Mean age of presentation in this study was 34 years. Radhika et al [3], Samaila et al [9], Saha et al [13], Rajalakshmi et al [15], El Ochi et al [16] also observed the same mean age. But Sharmaet al [14] got 40-60 years and Nair [17] got 10 -20 years.…”
Section: Resultsmentioning
confidence: 74%
“…Most of the tumors in this study were benign 98.8% while malignant was only 1.2%. Others studiesin which benign tumour predominance are Samaila et al [9], (88.5%), Radhika et al [3] (77.14%), Saha et al [13] (100%) Sharma et al [14] (80.36%), Rajalakshmi et al [15] (90.48%), El Ochi et al [16](97.7%), Nair [17] (100%) and Kaur et al [12]. Skin appendageal tumours are very difficult to diagnose.…”
Section: Resultsmentioning
confidence: 99%